Propagation of Bajakah and Akar Kuning to Support Bioprospecting of Traditional Medicine from Peat Swamp Forests: Prospect and Challenges - Hesti Lestari Tata; Septiana Asih Widuri; Noorcahyati; Antun Puspanti; Bina Swasta Sitepu; Mawazin (Institut Pertanian Bogor (IPB University), 2022)
Bajakah and akar kuning are known as traditional medicine from peatlands, which are usually extracted from their natural habitats. Over extraction and illegal cutting have become a threat to the extinction of both species. Therefore, propagation and cultivation of those medicinal plants are necessary to be conducted outside forest areas to meet the demand of raw materials of traditional medicine and minimize the risk of species extinction. The experiment of stem cutting propagation of two bajakah species (Uncaria acida and Salacia sp.) and akar kuning (Fibraurea tinctoria) were conducted separately in two different nurseries. The results showed that stem cuttings of woody liana could produce more than one new shoot. The new shoots of U. acida and Salacia sp. grew after eight weeks, with a survival rate of 96% and 50%, respectively. The survival rate of F. tinctoria stem cutting after six weeks was 83.3%. These indicate that bajakah and akar kuning can be propagated and cultivated to support the bioprospecting of traditional medicinal plants. Despite some challenges, such as limitation of akar kuning and bajakah population at the pole stage in their habitats, it is an initial step of a long process of bajakah and akar kuning bioprospecting.